Within-host evolution of HIV-1 and the analysis of transmissible diversity - English, SE (2012)
The central problem for researchers of HIV-1 evolution is explaining the apparent design of the virus for causing pandemic infection in humans: understanding how HIV-1 spreads is key to halting the pandemic. Current knowledge of how HIV-1 spreads from host to host is based upon experimental observation and indirect inferences informed by theory. The hypothesis of this thesis is that diversity of HIV-1 around the time of transmission is important for viral adaptation to a new human host, rather than intrinsic superiority of particular strains found in infectious fluids from human donor hosts, and that studying recombination is important for understanding this behaviour. To demonstrate the apparent randomness of transmission, I test the null-hypothesis that hard selection accounts for between-host viral divergence in a rare case study of contemporaneous infection. I explain how the experimental data that I have generated and the analyses I have carried out address certain basic assumptions and predictions about HIV-1 transmission and may inform current strategies for vaccine design. Specifically, my approach contributes to the current literature on HIV-1, by investigating an alternative hypothesis to the single virion theory of sexual transmission and by characterizing the role of recombination in a pseudodiploid virus following multiple-infection.